Majorana neutrinos in eγ colliders from an effective Lagrangian approach - Peressutti, Javier Hector (2014)
We study the production of heavy Majorana neutrinos (N) in e−γ colliders. We consider the tree-level process e−γ→W−N, which allows for lepton number violation via the decay N→l+2j. We follow the approach of an effective theory, where we consider all possible gauge invariant and nonrenormalizable operators of lowest dimension, which determine the interactions of the Majorana neutrino with the standard particles. We study the total cross section for different masses of the Majorana neutrino and different center-of-mass energies. We give an estimate for the range of the Majorana neutrino masses which may be detected in a e−γ collider.